Another Meir-Keeler-type nonlinear contractions - Francis, Daniel; Okeke, Godwin Amechi; Gibali, Aviv (AIMS mathematics, 2025)
This paper deals with the concept of $ α $-$ \hat{v} $-$ A $-$ B $-$ C $-Meir-Keeler type nonlinear contractions, a new class mappings within the of modular extended $ b $-metric spaces. We establish common unique fixed-point theorems that generalize, unify, and extend several key results in modular $ b $-metric and modular extended $ b $-metric spaces. These theorems bridge the gap between classical and contemporary fixed-point theories, showcasing broader applicability in nonlinear analysis. To ensure clarity and practical relevance, a detailed example is presented, further validating the theoretical findings. This work provides some level of understanding of the space under investigation and sets the stage for future developments in this evolving domain.